Political economy in the global south: Ecuador and Tanzania - Vásquez Arreaga, Jorge Daniel (CLACSO, 2021)
Political Economy of Knowledge implies the analysis of the production of knowledge and the role of actors, policies and programs which influenced higher education development during the developmentlism (1970’s), neoliberalism (1990’s), and the current period of transformation for higher education in the Global South. Ecuador and Tanzania share postcolonial histories and dependent economies that have given their universities prominent roles in the construction of their respective states, societies and national economies. Just as classrooms and studies at the Central University of Ecuador, the University of Dar-es-Salaam became a key player in the democratization of the country (Campuzano, 2005; Lulat, 2005). In the 1960s and 1970s, during the euphoric period following the Cuban Revolution and the independence of many African countries, universities in Latin America and Africa committed themselves to the struggles against political and social inequalities and strengthened their ties to popular sectors. These conditions have changed through next decades. From the standpoint of political economy, this research provides background for analyzing higher education in the context of the historical conditions in which capitalist accumulation and inequality have occurred at the global level. It also discusses the trajectory of the relationships among universities, politics and knowledge in Latin America and Africa, with special emphasis on Ecuador and Tanzania. The field work done at two rural universities, one in Ecuador and one in Tanzania. On the basis of work with documents and the positioning of various stakeholders (leaders, activists in social and educational movements, professors, politicians), the analysis makes it possible to understand the articulation between the production of knowledge within the universities and the shifts in designing educational plans within the frameworks of political disputes and the correlation of forces within the framework of globalization. We examine the 1960s to the 1980s, as Ecuadorian universities engaged with agrarian problems and professionalization, while higher education in Tanzania in that period aimed to serve development in the newly independent nation. We look, in particular, at the establishment of research and teaching agendas for the provincial public universities of the State University of Bolivar in Ecuador and Mzumbe University in Tanzania, to understand the ways that these peripheral instititutions defined and legitimized local knowledge in the context of national and global transformations. This research algo examine, the political economy of higher education in these two countries towards the end of the 20th century and into the 21st century. We analyze, on the one hand, the selected universities’ distinct local responses to the impacts of structural adjustment. In this section we also look at the ways that these universities have responded to the globalization of education in the 21st century, focusing on the importance of social sciences in the reconstruction of the State in the 20th century, in the context of a globalized economy.